دور مجلة الثقافية في نشر الثقافة الأسلامية دراسة على جمهور المجلة بسلطنة عمان - Batrani Juma Khalfan Saleh
The role of the magazine “Cultural” in the dissemination of Islamic culture study on the audience of the magazine.”Cultural” magazine is a quarterly cultural magazine, which is concerned with the dissemination of an authentic Islamic culture that works to enlighten the community, to visualize it with its rights, and its duties in a balanced manner and an enlightened discourse that takes from every art in ways that are means of spreading values, ethics,creed, spiritual education and balanced conscious thought that builds the individual,society and nation.This research was launched to determine the extent to which the cultural magazine was influenced by the intellectual,behavioural and intellectual values of the magazine’s readership,namely,teachers and students of the Islamic institutes of the Sultan Qaboos Higher Center for Culture and Science.This study aimed to identify the role of the Cultural Magazine in spreading Islamic culture to the audience of the audience of the magazine, teachers and students.The study community consists of teachers and students at the Sultan Qaboos Institutes of the Sultan Qaboos Higher Center for Culture and Science. This study was based on the analytical descriptive approach.In order to achieve the objectives of the study, the researcher used the questuinnaire as a data collection tool for abstracting and analyzing questionnaires using statistical analysis program (SPSS).The study reached the most important results: The role of the cultural magazine in the dissemination of Islamic culture from the point of view of teachers resulted in the highest role is the focus of the role of the magazine in the development of balanced Islamic thought and undermining its role to promote the areas of spiritual education, and that the magazine entrenched hearts in true love of God Almighty.The magazine seeks to establish the correct faith in the hearts of people.As for the role of the cultural magazine from the point of view of the students,it ranged from(3.81) at maximum of the first axis, which is the focus of the role of the magazine in the consolidation of the Islamic approach in the Islamic faith.This is evidenced by the ability of the magazine to reach students in the consolidation of Islamic doctrine.Nevertheless, the magazine lacks the development of values in the hearts of students.Further,this research contributes to building of a community of Islamic institutes of students and teachers in the Sultanate of Oman.